COSTS, PRICE AND PROFITS: ACCOUNTING IN THE WAR PROGRAM. - Kohler, E. L.; Cooper, W. W. (The Accounting Review, 1945)
The article presents information on accounting in the war program. War demands have made necessary central planning and control for the materials of war. Intelligent planning and control are dependent on accounting data. To obtain accounting data, recourse has been had to formal reports, questionnaires, surveys, telephone calls and conferences. Information secured has covered production, stocks, consumption, population and labor figures, costs and other financial and accounting statistics. In the stabilization and procurement programs, many new applications of accounting techniques have been devised. It is the purpose here to review a number of the more important accounting developments in the war program and to consider some of the possible long-range effects, particularly the use of accounting in establishing social controls. There have been long-standing requirements for accounting reports in income tax laws and various regulatory enactments. In addition, permissive legislation such as the Federal Trade Commission Act 2 demonstrates that Congress years ago had become aware of the necessity of financial reporting in the establishing of even the most general business controls.